USE OF CAMEL RATING FRAMEWORK: A COMPARATIVE PERFORMANCE ANALYSIS OF SELECTED COMMERCIAL BANKS IN INDIA - Kulshrestha, Preeti; Srivastava, Anubha (Copernican Journal of Finance & Accounting, 2022)
The performance of the banking sector is significant for any economy. The growth of a nation relies significantly upon efficient and optimum utilization of resources and also on operational efficiency of various sectors of an economy, of which the banking sector is a critical part. Banking system strengthens the stimulation of capital formation and provides liquidity. Indian banking sector comprises private, public, rural and foreign banks. In India, public sector banks are encountering challenges from private sector banks and are under constant pressure to perform better. Hence, this study endeavors mainly to analyze and compare the financial performance of the private and public banking sector by using CAMEL rating approach and for this purpose total of fourteen banks, representing the private and public, have been selected. The selected sample are the market leaders and have the highest market capitalization in the capital market. Overall, the paper aims to measure and compare the financial performance of private and public sector banks by employing CAMEL approach on their audited financial reports of eight years period i.e. (2011–2018). The ratios considered for this analysis includes Capital Adequacy (CA), Asset Quality (AQ), Management Soundness (MS), Earnings and Liquidity (LR). This study devised ranking method based on averages of various ratios and one way annova test is applied to find out statistical significance difference amongst groups. Results shown that private sector banks are better performers compare to Public sector bank. The overall results signify that the performance of private sector banks has improved because of the implementation of modern technology banking reforms and recovery mechanism.